PENGARUH MODEL THINK PAIR SHARE TERHADAP HASIL BELAJAR IPA SDN 36 PONTIANAK SELATAN - Apriani, Riska; Rosnita, Rosnita; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstarctThis study aims to determine whether there is influence of the use of Think Pair Share model to the learning outcomes of natural science students class V Public Elementary School 36 Pontianak Selatan. This research uses experimental method with quasy experimental design and experimental design of nonequivalent control group design. The sample in this research is 46 students, the sample selection is done randomly by conducting the drawing of all class VA (Control class) consisting of 23 students and class VB (Experiment class) 23 students. Instrument research in the form of test is multiple choice question form as much as 40 problems. From the result of this research, the mean value of post-test result of control class is 69,86 and average result of post-test of experiment class is 76,61. The result of hypothesis test using t-test obtained tcount = 2.027 with dk = 44 andÂ  5% obtained ttable = 2.017, which mean tcount (2.027) > ttable (2.017), thus Ha is accepted. From the calculation of effect size (ES), obtained ES of 0,95 (high category). So that learning by using model of â€œThink Pair Shareâ€ gives big influence to high result of learning of natural science students class V Public Elementary School 36 Pontianak Selatan. Â Keywords: Influence, Think Pair Share, Learning Outcomes